Routine deferred computed tomography for patients with suspected urolithiasis is low-value healthcare - Rosenlund, Ingvild Mathiesen; Førde, Olav Helge; Revhaug, Arthur (Scandinavian Journal of Urology, 2016)
Accepted manuscript version. Source at: https://doi.org/10.1080/21681805.2016.1254680 Objective - The aim of this study was to investigate the benefits of deferred routine computed tomography of the kidneys, ureters and bladder (CT KUB) for patients with a self-limiting episode of suspected urolithiasis. Materials and methods - The study comprised a case series of consecutive patients examined with deferred routine CT KUB for control of suspected urolithiasis. Patients examined with CT KUB at the University Hospital of North Norway, between 1 January 2010 and 31 December 2013, were included. The final analysis included 189 CT KUBs (response rate 48%). All data were extracted from the patient case files. The primary endpoint was the proportion of asymptomatic patients with a confirmed diagnosis of urolithiasis on CT KUB that led to surgical intervention within 1 year from the initial CT scan. Results - At the time of CT KUB, 171 patients (90%) were asymptomatic, of whom three (1.8%) were treated. Urolithiasis was confirmed on CT KUB in 23% of asymptomatic patients. Conclusion - Deferred CT KUB did not alter the clinical outcome for the great majority of asymptomatic patients. The majority of patients who received adequate pain relief in primary care remained asymptomatic, and did not need specialized healthcare. Refraining from CT KUB involves little risk. Deferred CT KUB for patients with suspected urolithiasis is a low-value healthcare service.